(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Most of the countries worldwide have strong regulations on drug markets, in order to cope with the rising costs of health care. On the other hand, the regulations violate the incentives for investment in pharmaceutical R&D projects. Thus, in order to stimulate R&D activity, and at the same time to regulate pharmaceutical market, every government is obligated to create balanced reforms for pharmaceutical market. This paper presents the policies for fostering innovations and regulations in the pharmaceutical market in R. Bulgaria and R. Macedonia. The comparison with the regulations and stimulations for pharmaceutical market in USA and other EU countries will help in creating the most corresponding programme, both for the customers and pharmaceutical companies. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.